Resilient design for London's elevated social spaces: exploring challenges, opportunities, and harnessing interactive virtual reality co-design approaches for community engagement - Abdelsalam, Ahmed Ehab (2023)
In the face of escalating urban density, the emerging concept of elevated urban spaces such as sky gardens and roof gardens is becoming a compelling requirement for human well-being in the process of densification. These spaces have gained additional significance in light of the adaptability and resilience required during the Covid-19 pandemic. This research explores the challenges and opportunities related to the design and management of such spaces, with a specific focus on London. A novel facet of this investigation is the application of Virtual Reality (VR) technology as a co-design tool, aimed at enhancing public engagement and the overall design experience of these spaces. The study emphasizes two particular urban locales in London: the Sky Garden and Crossrail Place, chosen for their unique design characteristics, public accessibility, and popularity. These case studies allow for an in-depth examination of critical design aspects such as accessibility, people flow control, pinch points, user experience, and the spectrum of activities that these spaces can accommodate. To create more sustainable and inclusive environments, the study leverages VR technology to bridge the gap between the physical and virtual worlds. This approach is aimed at understanding the impact of this integration on architectural and urban design processes, specifically in terms of design decision-making and its implications for the sustainability and longevity of public places. The adopted methodology is a phenomenological qualitative approach employing the Participatory Action Research (PAR) method. This involved direct observational studies, walk-along interviews with 33 visitors at each site, VR exploratory experiments with the same number of participants, and follow-up semi-structured interviews. Observations were conducted before, during, and after the Covid-19 pandemic, providing a comprehensive perspective on the unique challenges influencing the design and management of elevated urban spaces. The results indicate that VR, as a co-design tool, effectively promotes interactive public participation in the design process. The VR experiments facilitated users to identify design limitations and suggest improvements, even among participants who had not physically visited the sites. The concerns and needs identified through VR closely mirrored those expressed by actual users of the spaces. The findings also offer a comparative analysis of human activities, circulation patterns, and design considerations in both physical and virtual environments, highlighting the potential of VR technology for designing sustainable public spaces in a post-pandemic world. This research contributes threefold: (a) it furnishes theoretical input by establishing guidelines for the design of elevated social spaces, and provides empirical input by suggesting a range of design and planning considerations for developing active, pleasant, and resilient elevated social spaces; (b) it offers methodological input through the development of a multidisciplinary pragmatic framework for assessing the use of VR as an interactive co-design tool; and (c) it presents a comparative analysis of two advanced interactive VR approaches – Building Information Modeling (BIM) and gamification techniques – to enhance public engagement in public and social space design.